The Influence of Personal Selling and Education on Customer Interest in iB Maslahah Current Account Products at Bank BJB Syariah KCP Arcamanik. - Wazdi, Adi Indradi; Yulianti, Santi; Aprilia, Gadis Aisya (iora, 2023)
Based on the results observations, the background of this research is the lack of personal selling and the lack of education conducted at Bank BJB Syariah KCP Arcamanik, causing a lack of interest in current account products at the Bank. This study aims to find out how the influence of personal selling on customer interest in iB Maslahah current account products at BJB Syariah KCP Arcamanik bank partially and simultaneously. The object of research in this report is the interest of iB Maslahah current account customers at the BJB Syariah KCP Arcamanik bank. The type of research is quantitative associative, with primary data type and using data collection techniques in the form of observation, interviews, literature study, and questionnaires. While the sampling technique is incidental sampling, with a population of 173 people with a sample of 63 people who are iB Maslahah current account customers. The results of the study showed that there was is an insignificant effect between personal selling on the interest of current account customers at Bank BJB Syariah KCP Arcamanik by 9,9% with the results of the t-test where the value of t count>t table (2,572 > 1,670), there were There is a significant influence between education on customer interest in demand deposits at Bank BJB Syariah KCP Arcamanik by 4,4% with the results of the t-test where the value of t count>t table (2,497 > 1,670), and simultaneously there is a significant influence between personal selling and education on customer interest in the iB Maslahah current account product at Bank BJB Syariah KCP Arcamanik by 67% with the results of the F test where the value of f¬count->f¬¬table (4,927 > 3,15).